Strategi Industrialisasi Hubungan Dengan Sektor Lain - Danendra Bramantyo; Dinda Widya Kumala; Muhammad Yasin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research discusses industrialization strategies and their relationship with other sectors in the economy. Industrialization is an important economic transformation process, where a country or region shifts the economic focus from the agricultural sector to the industrial sector. An effective strategy in industrialization does not only focus on developing the industry itself, but also pays attention to the impact and interaction with other sectors, such as agriculture, services and technology. This research highlights the importance of synergy between sectors, economic diversification, and supportive government policies in creating a conducive environment for industrial growth. Through comparative analysis and case studies, this research finds that the success of industrialization is highly dependent on effective integration between the industrial sector and other sectors in the economy, as well as policies that support innovation and sustainable investment.